GENETIC VARIABILITY IN PROGENIES OF Eucalyptus grandis AND Eucalyptus urophylla FOR TOLERANCE TO HYDRIC DEFICIT - Chagas, Mateus; Siqueira, Leandro; Oda, Shinitiro; Medeiros, Raimundo; Tambarussi, Evandro Vagner (Floresta, 2018)
Genetic variability in progenies of Eucalyptus grandis and Eucalyptus urophylla for tolerance to hydric deficit. Information on the adaptation and genetic potential of Eucalyptus under water deficit conditions is necessary owing to the increasing cultivation of the genus in regions considered as "forest frontiers". Therefore, the present study aimed to estimate genetic variability, genotypic and phenotypic correlations, and estimated genetic gains in progenies of E. grandis and E. urophylla. Two progeny tests (TP1 and TP2) were performed in the municipality of Vila Nova dos Martirios (state of Maranhão, Brazil), in 30-month-old plants. The experiment was carried out using a randomized block design, with five replicates, nine plants/square plot, and 144 treatments in TP1 and 264 in TP2. Statistical analysis was performed and genetic parameters were estimated. Individual and within-progeny heritabilities were corrected using the kinship coefficient for each species. Genetic gains were low, ranging from 0.96 to 6.39% for E. grandis and 1.62 to 5.48% for E. urophylla. The diameter at breast height (DBH) showed a higher coefficient of genetic variation compared with the other measured characteristics, suggesting a higher potential for selection. High, positive, and significant correlations were observed between DBH and height (H), indicating the possibility of obtaining gains based on a single characteristic. Heritability was considered low, thus directly influencing the selection gains, which were lower than those commonly reported in other studies. These findings provide important information for breeding programs in areas of forest expansion.